Highly stretchable, electrochemical capacitance, and transparent supercapacitor based on serpentine-structured metallic mesh current collector - Zhouying Jiang; Yaoyao Zhao; Yanhua Liu (APL Materials)
Transparent and stretchable energy storage devices, maintaining the capability of steady operations under harsh conditions, have gained more importance with the development of transparent and stretchable electronics devices. Highly stretchable and transparent supercapacitors are essential for next-generation energy-storage systems with confluent high transparency, electrochemical stability, and mechanical properties during deformation processing. In this work, we report a transparent, flexible, and stretchable solid-state supercapacitor device with a serpentine-structured MnO2–Au–Ni mesh and a commercialized very high bond (VHB) tape; the stretchability of the hybrid electrode-based supercapacitor is significantly improved by shrinking the metallic mesh patched onto the VHB tape with pre-strain. The as-fabricated device exhibits an electrochemical capacitance of 3.64 mF/cm2 and an optical transparency of 73.63% at 300% strain. Furthermore, the device maintains 90.6% retention with strains up to 300% and 81.2% capacitance retention after 500 repeated stretch–release cycles at strains of 0%–300%. Along with the excellent tolerance to high deformation, the as-fabricated device can burden the desire for further wearable electronics.